Annoyance due to combined railway noise and vibration: Comparison and testing of results from the literature. (August 2020) - Maigrot, Philéas; Parizet, Étienne; Marquis-Favre, Catherine
Abstract: In situ surveys report some interactions between railway noise annoyance and the level of railway vibration on one hand, and between railway vibration annoyance and the level of railway noise on the other hand. Few studies have been conducted to investigate these interaction phenomena under laboratory conditions and their results are contradictory. During a laboratory experiment, recordings of noise and vibration from two train passages (1 freight train and 1 passenger train) were presented in combination to participants at different noise and vibration levels. The influence of noise level on participants' annoyance due to vibration, as well as the influence of vibration level on participants' noise annoyance was assessed in order to investigate two potential explanations for the contradictory results from the literature. Total annoyance responses due to combined noise and vibration were also analysed to further evaluate the influence of global noise and vibration levels on annoyance. No influence of vibration level on noise annoyance was detected. A weak influence of noise level on vibration annoyance was found, only when the vibration level was high ( L V eq = 116 dB). Several existing total annoyance models were tested. Among those, perceptual models showed good agreement with the laboratory data.